Kepemimpinan Manajerial Sebagai Upaya Mengurangi Turnover Intention Pegawai - Purnomoningrum, Sella Dyah; Mutiara, Nisa (Universitas Islam Kadiri, 2025)
This research aims to analyze managerial leadership, turnover intention , influencing factors, and company efforts to reduce turnover intention at Logistics Company in Kediri Region. This study uses a qualitative method with a descriptive approach. Data was collected through interviews, direct observation, and documentation from various informants, including 8 Hub Leaders at Logistics Company in Kediri Region. The results show that the leadership style at Logistics Company in Kediri Region combines transformational, democratic, and participative approaches, with effective managerial functions, although communication and decision-making processes need improvement. The turnover intention is relatively high, particularly among operational employees, due to job dissatisfaction, heavy workload, and limited career development. Managerial leadership is influenced by work experience, leadership style, and communication skills, while turnover intention is driven by job satisfaction, workload, compensation, and coworker relationships. The company has taken steps to mitigate turnover intention by improving communication, providing training, and revising compensation systems, though further efforts in career development and workload balance are required.